Cerium oxide nanoparticles attenuate the renal injury induced by cadmium chloride via improvement of the NBN and Nrf2 gene expressions in rats. Issue 2 (1st April 2022) - Bashandy, PhD, Mostafa M; Saeed, Hanan E; Ahmed, Walaa M S; Ibrahim, Marwa A; Shehata, Olfat
Abstract: Background: Cadmium (Cd) is a highly toxic heavy metal that adversely affects both human and animal health. Chronic cadmium exposure causes serious kidney damage. The current study investigated the protective role of cerium oxide nanoparticles (CeO2 NPs) against cadmium chloride (CdCl2 )-induced renal injury. Method: One hundred and twenty male albino rats were divided into 6 equal groups. Group (C): considered as control group which was given distilled water orally. Group (NC.1 and NC.5 ): rats were injected i.p. with nanoceria at a dose of (0.1 and 0.5 mg/kg b.wt), respectively, twice a week for 2 weeks starting at the 15th day of the study. Group (Cd): rats were received CdCl2 orally (10 mg/kg b.wt) daily for 28 days. Groups (Cd + NC.1 and Cd + NC.5 ): rats were given CdCl2 orally (10 mg/kg b.wt) for 28 days and CeO2 NPs by i.p. injection at a dose of (0.1 and 0.5 mg/kg b.wt), respectively, twice a week for 2 weeks started at the 15th day of the experiment. Results: The Cd group exhibited a significant increase in the serum levels of IL-1β, KIM-1, Cys-C, and β2-MG, downregulation of the antioxidant initiator genes such as Nrf-2, and up-regulation of apoptosis markers such as nibrin gene (NBN). Urine examination showed a high level of microalbuminuria, abnormal physical, chemical, and microscopical changes in comparison with control groups. Conculsion: Remarkably, posttreatment with CeO2 NPs showed significant improvement in kidney histopathological picture and relieved the alterations in kidney biomarkers, inflammatory markers, urine abnormalities, and expressions of different genes as Nrf-2 and NBN.